Strictly webbed spaces and regularity properties of inductive limits - Armando García-Martínez (International Journal of Mathematics and Mathematical Sciences)
Sequentially complete, locally complete, locally Baire, and bornivorously webbed are equivalent for strictly webbed spaces. For inductive limits of strictly webbed spaces these properties are equivalent. Moreover, they imply regularity.